2014
DOI: 10.1590/1516-1439.302614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polystyrene on poly(ethylene terephthalate) crystallization

Abstract: Blends of poly(ethylene terephthalate) (PET) and polystyrene (PS) with PS content ranging from 0% to 60% by weight, were compounded in a laboratory internal mixer, followed by quenching into iced water, resulting in substantially amorphous compounds. Blend morphology was analyzed by scanning electron microscopy (SEM). Standard differential scanning calorimetry (DSC) was used to study the cold crystallization and melting behavior of PET and PET/PS blends. SEM micrographs show a two-phase structure made up with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Further research [ 29 ] indicated that by blending atactic polystyrene into the polyester, higher amorphicity could be achieved. Therefore, polystyrene and poly‐H were added together in the alumina DSC pan, heated and quenched in liquid nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Further research [ 29 ] indicated that by blending atactic polystyrene into the polyester, higher amorphicity could be achieved. Therefore, polystyrene and poly‐H were added together in the alumina DSC pan, heated and quenched in liquid nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reduction of Δ H cc and Δ H m explains why crystallization is difficult. This difficulty as expressed by the reduction in the PHBV degree of crystallinity resulting from EVA addition, which represents a perturbation to the crystalline ordering . PHBV/EVA65 blends containing at least 80 wt% EVA65 showed no cold crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…This difficulty as expressed by the reduction in the PHBV degree of crystallinity resulting from EVA addition, which represents a perturbation to the crystalline ordering. [15] PHBV/EVA65 blends containing at least 80 wt% EVA65 showed no cold crystallization. The DSC curves of PHBV/EVA65 blends with EVA content varying between 10 and 80 wt% exhibited two melting points.…”
Section: Macromolecular Symposiamentioning
confidence: 96%
“…Crystallization can have a tremendous impact on fiber mechanical properties, and can also be affected by fiber composition. Wellen et al found that the addition of even small amounts (1 wt %) of PS to PET reduced the rate of cold crystallization or crystallization upon heating due to the anti-nucleating effect of PS on PET, although the ultimate degree of crystallinity was not affected [ 25 , 26 ]. In our work, we found that the degree of crystallization was reduced by blending with 50 wt % PS.…”
Section: Discussionmentioning
confidence: 99%
“…If the crystallinity is too high, stretching during the blow molding cycle may be impaired, while too low crystallinity can result in reduced barrier and mechanical properties. The addition of PS and displacement of the crystallization peak to higher temperatures can contribute to a wider range of cold crystallization phenomena from the segregation between PS and PET molecules [ 25 , 26 ]. The introduction of 1–20 wt % PS caused a shoulder on the crystallization peak in Wellen’s studies, indicative of at least two crystallization phenomena such as different crystalline geometries, but this was not observed in our studies.…”
Section: Discussionmentioning
confidence: 99%